STABILITY ANALYSIS IN EQULIBRIUM OF THE DEMAND AND SUPPLY FOR WHEAT CROP IN IRAQ DURING THE PERIOD 1971-2013USING COBWEB MODEL - & AL-HIYALI, AL-DAAMI (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2017)
The wheat crop consider one of the main important crops in the world, and it is occupied the first order in importance, it is one of the winter grains crop in Iraq, and the Iraqi family cannot leave it because its nutritional gains besides its economic importance. The agricultural policies those follow by the government are influence positively or negatively on the agricultural production; therefore we should focus on evaluating these consequences. The study aims estimating the demand and supply functions for the wheat crop in Iraq and analyzing the stability in equilibrium system of the demand and supply for the crop during the period (1971-2013), besides evaluating consequences of the agricultural pricing policy in the short and long run by using the cobweb Equilibrium Model (CEM). the study depends on many variables in the equilibrium analysis model those contributing in knowing influence of the governmental policies, repressed by the consumed quantities of wheat, supplying quantities, prices of wheat, the national income in fixed prices, the population and prices of the inputs (price of the fertilizer), in both of them we using the double logarithmic model to represent the relationship between the dependent variable and the independent variables, the study reached to that the satisfaction obtained from the wheat consumption was high because decreasing of the income elasticity which was (0.004), furthermore the positive signal it indicate that the wheat is normal and necessary good, the results show that the satiated obtained from the wheat consumption was high, the results of the function of supply show that response of the farmer to the changing in prices was weak, and this indicate weakness in performance of the locally governmental pricing policy, and concerning with price of the fertilizer, the results show that the farmers do not using this input economically and about results of the an equilibrium analysis they came to support the results in the first analysis, the results of the coefficients in the long run came stable with results of the short run, while results of the stability of the equilibrium show that role of pricing policy causing un equilibrium in the demand and supply system of the wheat (then equilibrium unstable) while the system was relatively stable in the long run, and the national income, population were have positive influence in increasing the demand quantities, the study reached to set of recommendations at the end of the search.